Measuring cerebral hemodynamics and oxygen metabolism indices using NIR-TRS in premature infants from birth to term-equivalent age - Shonosuke Nara; Midori Nishibata; Maria Nishibukuro; Naofumi Hanyu; Soken Go; Hironobu Okuno; Shinji Nakamura; Takashi Kusaka; Gaku Yamanaka (Scientific Reports)
Abstract Central nervous system development influences the neurological prognosis of premature infants, and their management may be better guided by the evaluation of the oxygen supply-demand balance in brain tissue. Near-infrared time-resolved spectroscopy (NIR-TRS) can measure cerebral oxygen metabolism indices, including cerebral blood volume (CBV), as absolute values. Cerebral hemoglobin oxygen saturation (ScO2) and the cerebral tissue oxygen extraction rate (cFTOE), but not CBV, have been reported in premature infants. Here, we used NIR-TRS to evaluate the longitudinal changes in these indices, including CBV, in 26 extremely premature infants born at < 30 weeks’ gestation without intracranial hemorrhage. ScO2 was very slightly negatively correlated with postnatal week (r = − 0.19, p < 0.001). The cFTOE increased with postnatal week (r = 0.37, p < 0.001) and postconceptional week (r = 0.81, p < 0.001) while CBV decreased with postnatal week (r = − 0.34, p < 0.001) and postconceptional week (r = − 0.90, p < 0.001). This study is the first to prospectively evaluate changes in CBV after birth in preterm infants without intracranial hemorrhage. Our results show that the cerebral oxygen demand of preterm infants increases with postnatal week but that the growth of the cerebral vascular bed may be delayed.